2015
DOI: 10.1523/jneurosci.5023-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neural Networks Reveal a Gradient in the Complexity of Neural Representations across the Ventral Stream

Abstract: Converging evidence suggests that the primate ventral visual pathway encodes increasingly complex stimulus features in downstream areas. We quantitatively show that there indeed exists an explicit gradient for feature complexity in the ventral pathway of the human brain. This was achieved by mapping thousands of stimulus features of increasing complexity across the cortical sheet using a deep neural network. Our approach also revealed a fine-grained functional specialization of downstream areas of the ventral … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
520
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 860 publications
(558 citation statements)
references
References 53 publications
36
520
2
Order By: Relevance
“…Of course, we might also expect some differences in the development of object recognition across species, especially between chickens and humans. For instance, humans have much larger visual systems than chickens, which may allow humans to achieve greater levels of abstraction across the successive levels of the visual cortex [36,37,44]. Further, chickens, unlike humans, are mobile from birth and immediately able to explore their environment.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, we might also expect some differences in the development of object recognition across species, especially between chickens and humans. For instance, humans have much larger visual systems than chickens, which may allow humans to achieve greater levels of abstraction across the successive levels of the visual cortex [36,37,44]. Further, chickens, unlike humans, are mobile from birth and immediately able to explore their environment.…”
Section: Discussionmentioning
confidence: 99%
“…A number of BOLD-MRI studies have revealed that the neural activation's in early areas of visual cortex show the best correspondence with the early layers of DNNs and that higher-tier cortical areas show the best correspondence with higher-tier DNN layers (Eickenberg, Gramfort, Varoquaux, & Thirion, 2017;Gü çlü & van Gerven, 2015). MEG/EEG studies have furthermore shown that early layers of DNNs have a peak explained variance that is earlier than higher-tier DNN layers (Cichy, Khosla, Pantazis, Torralba, & Oliva, 2016;Ramakrishnan, Scholte, Smeulders, & Ghebreab, 2016).…”
Section: 1mentioning
confidence: 99%
“…The structure and operation of a neuron-the basic building block of ANN-have been described on several occasions (Guclu et al 2015). Briefly, it is a cascaded design, from an input layer to an output layer, where functional blocks are sandwiched either between input and hidden, or hidden and output layers, where each layer may comprise a specific number of neurons.…”
Section: Artificial Neural Network Modelmentioning
confidence: 99%